2024
DOI: 10.1186/s12877-024-04684-0
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between dysphagia and frailty among Chinese hospitalized older patients: a serial mediation model through self-perceived oral health and self-reported nutritional status

Jianjiao Yu,
Huolan Zhu,
Yulian Zhang
et al.

Abstract: Background Frailty contributes to adverse outcomes in older adults and places a heavy burden on healthcare resources. Dysphagia is associated with frailty, but the mechanisms by which dysphagia affects frailty in older adults are unclear. This study aimed to investigate a serial mediating effect of self-perceived oral health and self-reported nutritional status in the relationship between dysphagia and frailty among hospitalized older patients in China. Methods … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 48 publications
0
1
0
Order By: Relevance
“…The professional groups carrying out the screenings were reported in only 6 studies (Nursing staff/study nurse: Cabre et al 2010; Carrión et al 2015; Mateos-Nozal et al 2017; Shimazu et al 2020; SLT: Crary et al 2006; Moncayo-Hernandéz et al 2023) [ 10 , 43 46 , 49 ]; 7 studies used exclusively self-reported tools (Manas-Martinez et al 2018; Matsuo et al 2017; Popman et al 2016; Tran et al 2021; Vidal Casariego et al 2020; Wakabayashi & Matsuhima 2016; Wham et al 2017) [ 41 , 47 , 50 , 57 , 58 , 60 , 67 ] and the remaining 14 did not specify the profession [ 13 , 42 , 48 , 51 56 , 59 , 61 , 68 70 ].…”
Section: Resultsmentioning
confidence: 99%
“…The professional groups carrying out the screenings were reported in only 6 studies (Nursing staff/study nurse: Cabre et al 2010; Carrión et al 2015; Mateos-Nozal et al 2017; Shimazu et al 2020; SLT: Crary et al 2006; Moncayo-Hernandéz et al 2023) [ 10 , 43 46 , 49 ]; 7 studies used exclusively self-reported tools (Manas-Martinez et al 2018; Matsuo et al 2017; Popman et al 2016; Tran et al 2021; Vidal Casariego et al 2020; Wakabayashi & Matsuhima 2016; Wham et al 2017) [ 41 , 47 , 50 , 57 , 58 , 60 , 67 ] and the remaining 14 did not specify the profession [ 13 , 42 , 48 , 51 56 , 59 , 61 , 68 70 ].…”
Section: Resultsmentioning
confidence: 99%